IS THE ORGANIZATION CULTURE OF HIGH EDUCATION FRIENDLY FOR WOMEN RESEARCHERS IN LITHUANIA? - Šidlauskienė, Virginija; Šaparnienė, Diana; Kovierienė, Ala (Acta Paedagogica Vilnensia, 2008)
The number of women in the fields of high education that involve and deal with Engineering & Technology (E&T) has always been smaller than men’s. Some feminists explain this phenomenon by pointing out the manner in which the terminologies, methodologies and relationships between dominant majority group (Euro men) and “different” / “other” social identity group (Euro women) of these research fields have been recognized as central issues affecting the advancement, legitimacy and survival of organizations themselves. This strand of feminist research has underlined the masculine aspect of technology socially constructed on the exclusion of women from engineering and technological domains. Soon enough this analysis has become a mainstream foundation for the strategies that attempt to transform organizational cultures of these fields so as to make them friendlier to women in Lithuanian educational environment. [...]
Keywords: ...